2015
DOI: 10.1007/s00198-015-3365-x
|View full text |Cite
|
Sign up to set email alerts
|

Proton-pump inhibitors and risk of fractures: an update meta-analysis

Abstract: In this update meta-analysis of observational studies, PPI use modestly increased the risk of hip, spine, and any-site fracture, but no evidence of duration effect in subgroup analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
157
0
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(169 citation statements)
references
References 38 publications
6
157
0
6
Order By: Relevance
“…Additionally, PPI use has been linked to osteoporosis and fractures. A recent meta-analysis of 18 observational studies found 58%, 26%, and 33% greater risk of spine fracture, hip fracture, and fracture at any site, respectively, among PPI users compared to nonusers [86]. …”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…Additionally, PPI use has been linked to osteoporosis and fractures. A recent meta-analysis of 18 observational studies found 58%, 26%, and 33% greater risk of spine fracture, hip fracture, and fracture at any site, respectively, among PPI users compared to nonusers [86]. …”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…PPI users (even after short-term, i.e.<1 year) showed modestly higher risks of bone fractures, of hip (26%), of spine (58%), and of any site (33%), according to a meta-analysis of 18 studies (Zhou et al, 2016). FDA published a safety alert in May 2010 about possible increased risk of the hip, wrist, and spine, which was updated in March 2011 (FDA, 2012).…”
Section: Bone Fracturesmentioning
confidence: 99%
“…Dementia [14] Osteoporosis and fracture [19] Kidney disease [16] Gastrointestinal [18] and prulmonary [15] RR relative risk, CI confidence interval, OR odds ratio, CAP community-acquired pneumonia, CKD chronic kidney disease, AIN acute interstitial nephritis, GRADE grading of recommendations assessment, development, and evaluation…”
Section: Key Messagesmentioning
confidence: 99%
“…Although a critical review of the relevant literature does demonstrate associations between PPIs and serious skeletal, renal, gastrointestinal, and neurological events, these findings are based on epidemiological evidence. In Table 1, a summary of the criteria proposed by Bradford Hill for assessing causality and the association between PPIs and adverse events are presented; much of the data are weak and potentially subject to major bias including confounding [14][15][16][17][18][19]. Notably, no reports of hypomagnesemia due to acid-suppressing medications were described by Bielefeldt, despite this being a recognized adverse effect of PPI, probably due to its extreme rarity [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation